PERAN SISTEM TEKNOLOGI INFORMASI DENGAN EFISIENSI OPERASIONAL BANK SYARIAH MODERN - Nyak Angeli Ajianing; Maulia Riska; Nurbaiti (STAI Denpasar Bali, 2025)
This study aims to analyze the role of information technology systems in enhancing operational efficiency in modern Islamic banks. The implementation of information technology is considered essential for accelerating services, improving data accuracy, reducing administrative costs, and expanding the reach of digital financial services in the Islamic banking sector. This research employs a qualitative approach to explore processes, experiences, and the application of digital services in several Islamic banks that have implemented mobile banking, internet banking, and IT-based internal management systems. The findings reveal that information technology significantly improves operational efficiency and effectiveness through transaction digitalization, administrative process automation, mobile banking utilization, e-procurement systems, integration of digital payment features, and the adoption of fintech solutions. Information technology also strengthens data security and enhances service quality for customers. However, its implementation presents challenges such as cybersecurity risks, infrastructure readiness, human resource competence, and compliance with Sharia principles. Overall, the application of information technology systems contributes substantially to improving efficiency, productivity, and competitiveness in modern Islamic banking.